2000
DOI: 10.1590/s0004-27492000000600009
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo da acomodação residual após instilação de colírios de tropicamida a 1%, ciclopentolato a 1% e associação de tropicamida a 1% + ciclopentolato a 1%

Abstract: Estudo comparativo da acomodação residual após instilação de colírios de tropicamida a 1%, ciclopentolato a 1% e associação de tropicamida a 1% + ciclopentolato a 1%Objetivo: Avaliar a acomodação residual após a instilação de duas drogas cicloplégicas, o ciclopentolato a 1% e a tropicamida a 1% e a associação entre elas.Material e Método: Selecionamos pacientes de 15 a 25 anos, com íris grau 4 e 5 pela classificação de Seddon e sem nenhum tipo de doença ocular, que procuraram de maneira espontânea o ambulatóri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(27 reference statements)
1
2
0
3
Order By: Relevance
“…Our results demonstrated no differences in spherical equivalent between TCP and CP, confirming that any additional cycloplegic effect exerted by tropicamide was trivial compared with that of cyclopentolate. 18 Further, this trend was observed among all types of refractive error, including high hyperopia in excess of 13.00 D. These findings are consistent with Zetterstr€ om, 19 who argued that the use of two different short-acting parasympatholytic drugs would be unnecessary, given that cyclopentolate and tropicamide block the action of acetylcholine at the same receptors. Recognizing cyclopentolate's well-documented efficacy as a cycloplegic on its own, 2,5 it is logical to expect any further influence from the less potent tropicamide to be negligible.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results demonstrated no differences in spherical equivalent between TCP and CP, confirming that any additional cycloplegic effect exerted by tropicamide was trivial compared with that of cyclopentolate. 18 Further, this trend was observed among all types of refractive error, including high hyperopia in excess of 13.00 D. These findings are consistent with Zetterstr€ om, 19 who argued that the use of two different short-acting parasympatholytic drugs would be unnecessary, given that cyclopentolate and tropicamide block the action of acetylcholine at the same receptors. Recognizing cyclopentolate's well-documented efficacy as a cycloplegic on its own, 2,5 it is logical to expect any further influence from the less potent tropicamide to be negligible.…”
Section: Discussionsupporting
confidence: 79%
“…16 While many continue to recommend TCP, 15,17 the added benefit of tropicamide remains dubious. 18,19 One study found no significant difference in accommodative amplitude or pupil diameter between a TCP solution and CP control, suggesting that any effect induced by tropicamide was negligible in comparison to that of cyclopentolate and phenylephrine. 20 It is important to note, however, that this study was conducted in adults and may, consequently, not be generalizable to children, who possess greater amplitudes of accommodation and require more potent cycloplegic agents.…”
mentioning
confidence: 99%
“…The total hyperopia was evaluated with the same refractor 40 min after the instillation of Cyclopentolate 1%. Over recent years, several studies comparing the cycloplegic effect of various drugs to the required number of drops have proved that the instillation of a drop of Cyclopentolate 1% is sufficient to obtain adequate cycloplegia (10)(11)(12)(13) . The individuals were requested to return one week after the refractive evaluation for an accommodative effort task.…”
Section: Methodsmentioning
confidence: 99%
“…A cicloplegia foi conseguida pela instilação de 1 gota do colírio de ciclopentolato a 1% (Cicloplégico ® , Allergan, São Paulo) e, após intervalo de 5 minutos, 1 gota do colírio de cloridrato de tropicamida a 1% (Mydriacyl ® , Allergan, São Paulo) em cada um dos dos olhos (19) .…”
Section: Métodosunclassified